2019
DOI: 10.1177/1367493518814922
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea can be used in children with sickle cell disease and cerebral vasculopathy for the prevention of chronic complications? A meta-analysis

Abstract: We conducted a systematic review for evaluating the impact of hydroxyurea and chronic blood transfusion in children with sickle cell disease (SCD). A search was done in four databases from inception to 2017. Trials enrolling pediatric patients with SCD and cerebral vasculopathy with or without previous episode of stroke and that reported outcomes of occurrence of stroke and other events were included. Trained reviewers determined eligibility, risk of bias, and abstracted data. Random-effects meta-analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The aim of the therapy is to maintain hemoglobin S <30%, as red blood cells increase the total volume of hemoglobin, consequently increasing oxygen saturation and decreasing the percentage of hemoglobin S. 1 The treatment, despite side effects such as iron overload, alloimmunization, transfusion reactions, and increased risk of thrombosis and mortality, constitutes currently the only proven strategy for secondary prevention of stroke, although it is not widely used. 1,4,24 More than 45% of patients may experience ischemic strokes despite regular transfusions. 26 Nevertheless, a systematic review showed that hydroxyurea was not superior to regular blood transfusion for reducing neurological events in children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of the therapy is to maintain hemoglobin S <30%, as red blood cells increase the total volume of hemoglobin, consequently increasing oxygen saturation and decreasing the percentage of hemoglobin S. 1 The treatment, despite side effects such as iron overload, alloimmunization, transfusion reactions, and increased risk of thrombosis and mortality, constitutes currently the only proven strategy for secondary prevention of stroke, although it is not widely used. 1,4,24 More than 45% of patients may experience ischemic strokes despite regular transfusions. 26 Nevertheless, a systematic review showed that hydroxyurea was not superior to regular blood transfusion for reducing neurological events in children.…”
Section: Discussionmentioning
confidence: 99%
“…The review also associated regular blood transfusions with a lower risk of vaso-occlusive crises and found no difference for the occurrence of more serious adverse events when compared to hydroxyurea. 4 A Cochrane review was unable to show whether regular blood transfusion, for at least 1 year, differed in relation to the use of hydroxyurea for primary or secondary prevention of stroke in children at risk of stroke with abnormal transcranial Doppler and no vasculopathy. 27 In the present study, information regarding blood transfusions was not found in 3 patients (21.4%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a meta-analysis published in 2020, where only the SWiTCH trial had the necessary inclusion criteria to answer whether HU could replace monthly blood transfusions in secondary stroke prevention, the conclusion was that for children with SCA and a history of cerebrovascular abnormality, transfusions should be used together with iron chelation therapy. 37 (D) However, a Cochrane Database of Systematic Reviews meta-analysis concluded that only the SWiTCH trial is not enough to establish that the HU and phlebotomy increased the risk of stroke [RR 14.78 (95%CI 0.86 -253.66)] or mortality [Peto OR 0.98 (95%CI 0.06–15.92)], compared to pRBC transfusions and iron chelation. 38 (D)…”
Section: Clinical Questionsmentioning
confidence: 99%